L'apertura - Hutchinson, G (Edizioni Tored, 2021)
The act of opening a box, door, etc. was important to ancient practical life; poetry exploits it forcefully, and with rich psychological and theological significance. Spring is often connected with opening (so Alcaeus, Pindar, Ovid). Scenes of opening, and not opening, are important in the Odyssey and Parmenides, in drama (Agamemnon, Ajax, Medea, Heracles, Ion, Clouds, Ecclesiazusae, Curculio), in Hellenistic poetry (Apollonius, Theocritus, Grenfell Fragment), and in Roman poetry (Odes, Amores, Aeneid). Chests and boxes can contain memories and link to the opening of emotions; drama interests itself in revealing closed thoughts, secrets, and events. Door-scenes dramatize the conflict of wills in plays and poems on love. The drastic interventions of the gods are manifested and expressed through opening.